10. MENELUSURI TINDAK KEKERASAN DI TANAH AIR - Turtiantoro, Turtiantoro (FORUM, 2008)
History of Indonesian nation up to now notes various grieves, misery and social difference, which caused by unjust behavior and discrimination on the basis of ethnic , race, skin colour, culture, language, religion, faction, gender, and other social status. Unjust behavior and discrimination is human right collision.